Adjuvant psychotherapy in early-stage bipolar disorder: study protocol for a randomized controlled trial - Thomas J. Stamm; Julia C. Zwick; Grace O’Malley; Lene-Marie Sondergeld; Martin Hautzinger (Trials, 2020)
Abstract Background Bipolar disorders are serious illnesses with a chronic course and a high rate of relapse. Typically, bipolar disorders onset during adolescence or early adulthood, with patients experiencing significant personal and social costs as a consequence of their illness. Despite this, to date, there is limited (controlled) evidence regarding the effectiveness of psychotherapy during the critical stages of the disorder (e.g., early onset). Some preliminary studies suggest that targeted, tailored early interventions in particular may improve disease prognosis. The proposed study examines the effectiveness of group psychotherapy on relapse prevention, global adaptive functioning, and neuropsychological functioning in early-stage bipolar disorder. Methods In this multicenter randomized controlled trial (RCT), 300 patients with bipolar disorder are randomized to one of two group psychotherapies: Specific Emotional-Cognitive Therapy (SECT; intervention group) or Emotion-Focused Supportive Therapy (EFST; active control group). Each therapy comprises of a total of 48-h sessions (delivered once a month) over a period of 4 months. Assessments take place at baseline (t1); 6 months follow-up, i.e., post-intervention (t2); 12 months follow-up (t3); and 18 months follow-up (t4), whereby 18 months follow-up is the primary time point of interest. Discussion The goal of this study is to test the effects of an innovative, specific group therapy relative to an active control condition in terms of rates of relapse, global functioning, and neuropsychological functioning. Pending the outcomes of the trial, it will be possible to establish a firm evidence base for accessible group psychotherapy adjuvant to routine psychiatric care for individuals with bipolar disorder. Trial registration USA: ClinicalTrials.gov NCT02506322 . Registered on 19 December 2014; Germany: German Clinical Trials Register DRKS00006013 . Registered on21 May 2015